Mecz bokserski między S.K.S "Czytelnik" Gdynia - Z.K.S. "Stoczniowiec" Gdańsk. (Gdynia : [s.n.], 1947)
Afisz inf. o meczu 23.03.1947 r.
Keywords: Stocznia Gdańska -- 1945-1970 -- druki ulotne; Boks -- Polska -- Gdańsk -- 1945-1970 -- druki ulotne; Gdańsk (Polska) -- 1945-1970 -- druki ulotne